Dual role of Zn2+ as inhibitor and activator of fructose 1,6-bisphosphatase of rat liver. - Tejwani, G A (1976)
At neutral pH, Zn2+ is a potent and specific inhibitor of rat liver fructose 1,6-bisphosphatase (EC 3.1.3.11; D-fructose-1,6-bisphosphate 1-phosphohydrolase). Inhibition by Zn2+ is uncompetitive with respect to the activating cations Mg2+ and Mn2+, and the kinetic data suggest that the enzyme possesses a distinct high-affinity binding site for Zn2+, with Ki of approximately 0.3 muM. At higher concentrations (about 10(-5) M) Zn2+, and to a lesser extent Co2+, function as activating cations. Binding studies show that the enzyme binds two equivalents of Zn2+ per subunit; one equivalent is partially displaced by Mg2+ and is presumably bound to the site for activating cations. A second equivalent binds to the high-affinity site, presumably identical to the inhibitory site. The results suggest that Zn2+ functions as an allosteric regulator, and that the commonly observed activation of fructose 1,6-bisphosphatase at neutral pH by EDTA, histidine, and other chelators is due to removal of endogenous Zn2+ by these agents.